Studi Kerentanan Air Tanah Terhadap Kontaminan Di Cekungan Airtanah Negara Kabupaten Jembrana Provinsi Bali - Frederich Gunawan, Wayan Andi; Sisinggih, Dian; Dermawan, Very (Fakultas Teknik, Universitas Brawijaya, 2013)
The government of Jembrana Regency will exploit the groundwater to develop area potency. Seven thematic maps of the DRASTIC and SINTACS method were developed in order to asses the vulnerability of groundwater to contaminate and these include the depth to water table, recharge, aquifer media, soil media, topography, impact of vadose zone and hydraulic conductivity. Determination of the DRASTIC Index (DI) and SINTACS Index (SI) was done by multiplaying each parameter weight by its value rating and summing the total. Based on DI and SI values, a groundwater vulnerability map was produced using a Geographical Information System (GIS). The Result of this research is groundwater vulnerability in Negara groundwater basin consisted of medium to very high groundwater vulnerability. SINTACS Method is more suitable with the parameter of research location. The result of this research shown that Medium vulnerability is in a part of north Negara ground water basin, while in south area is dominated by high vulnerability level. It is mean that the parameter is give significant impact to the value are included recharge, soil media and topography. Jembrana regency area especially in north area is needed special treatment due to high potency of groundwater vulnerability.Keyword : Groundwater vulnerability, DRASTIC, SINTACS .